Papillary carcinoma in a thyroglossal cyst: a rare case report and review of literature - Ravichandran, Subhashini Puducherry; Ganesan, Sivaraman; Raja, Kalaiarasi; Alexander, Arun; Saxena, Sunil Kumar (International Surgery Journal, 2020)
Thyroglossal cysts are the most common thyroid anomaly with a majority of it being diagnosed at fourth decade of life. Authors report a case of 32-year-old lady with a globular swelling of 3×2 cm moving with deglutition with no cervical lymph nodes and a normal thyroid function test. Intra operatively a distinct lesion of 3×2 cm was found superior to the thyroid gland with firm nodules in the right lobe of the thyroid. Patient underwent total thyroidectomy with central compartment neck dissection and Sistrunk’s operation followed by a negative radio iodine scan and thyroid hormone suppression. This was considered based on intraoperative nodularity of the thyroid gland.